ARKEOLOGI, DUNIA PENDIDIKAN, OTONOMI DAERAH DAN JATI DIRI - Hari Lelono (BRIN, 2006)
The current concern of the Indonesian people is the decline in the morale of the nation. Why this happens, of course, is our problem together. One of the things accused of being the main cause may be the world of education. The ever-changing educational system is still looking for the ideal form. As a result, students become victims, besides that the material does not refer to the power of a multi-ethnic and multicultural nation. It was time for cultural observers; archaeologists and historians to think about this diverse cultural material in order to become one of the educational materials with the insight of Indonesian culture on a regional and national scale.